El papel de la actividad experimental en la ordenación de cualidades y construcción de fenomenologías - Sandoval Osorio, Sandra; Malagón Sánchez, José Francisco; Ayala Manrique, María Mercedes (Revista Científica, 2011)
This text reflects on the role of experimental activity in the arrangement of certain qualities in the establishment of measurement scales and measuring instruments, as well as the construction of languages to discuss some phenomenological study. For the research group is particularly relevant to study the routes by which experimental activity contributes to construction relations between magnitude that are developed, the phenomenological organization and production processes of generalization and of theorizing about phenomenology studied or new phenomenology to study. Since these criteria have been proposed a discussion about the pedagogical and cognitive criteria from which to design and implement experimental activities that influence the understanding of phenomenology. Generation in the field of science education of the link between organizational processes of phenomenology, the processes of formalization and experimental activity is mediated by the solution to the question: how to characterize the linkage relationships between variables and theorizing is made of a phenomenal field with the cognitive processes and teaching in the classroom?